Pencil Lead Electrode Termodifikasi Lapisan Tipis Perak Untuk Deteksi Ion Logam Cd2+ Dengan Metode Voltammetri - Fadiah; Trisna Kumala Sari (Journal of Research and Education Chemistry, 2024)
Cd2+ metal ions are contaminants that threaten the environment and human health. The purpose of the study is to study the electrochemical responses of PLE and Ag/PLE to detect Cd2+ metal ions, as well as to determine the best supporting electrolyte condition for measuring Cd2+ ions. The cyclic voltometric method is used to modify the electrodes by depositing a thin layer of silver. The results of the study show that Ag/PLE is better for detecting Cd2+ ions compared to PLE. The optimum conditions were obtained with a supporting electrolyte of acetate buffer pH 4.